A retrospective cohort survey of problems related to second childbirths during the 2-child policy period in Jiangbei District of Ningbo City in China. Issue 18 (May 2018) - Fu, Jun; Qu, Yu; Ji, Fei; Li, Huijuan; Chen, Fangyuan
Abstract : Abstract: From 1979 to 2014 in China, a 1-child policy was imposed to control population growth. During 2014 to 2015, families in which 1 spouse was only 1 child were eligible to apply for planning a second child. To foresee issues affecting obstetrical departments related to the introduction of the universal 2-child policy in 2016, we retrospectively investigated the demographics and health-related outcomes of second pregnancies in families applying for a second child in Jiangbei District of Ningbo City during January 17, 2014, to January 14, 2016. A retrospective cohort survey was conducted for Jiangbei District of Ningbo City from January 17, 2014, to January 14, 2016, with reference to data from 2012 to 2014. Applications for a second birth increased after implementation of the 2-child policy, from 505 in 2012 to 2013, to 1222 in 2014 to 2015. Until the end of this study (December 31, 2016), 739 women gave birth to a second child, among whom 21.38% were aged ≥35 years. Rates of cesarean deliveries (59.68%) and gestational diabetes mellitus (14.21% of women) were each positively associated with the age of the mother. Among women aged ≥35 years, 37.97% refused prenatal screening. Introduction of the 1-child policy encouraged more families to apply for a second child, with many women aged ≥35 years, leading to higher rates of cesarean deliveries and adverse complications. A high percentage of eligible older women refused prenatal screening. Obstetric departments should adjust perinatal health management schemes to prepare for similar probable changes associated with the universal 2-child policy.